Immune Challenge Alters Reactivity of Hippocampal Noradrenergic System in Prenatally Stressed Aged Mice - Gayane Grigoryan; Niklas Lonnemann; Martin Korte (Neural Plasticity)
Prenatal stress (PS) has long-term sequelae for the morphological and functional status of the central nervous system of the progeny. A PS-induced proinflammatory status of the organism may result in an impairment of both hippocampal synaptic plasticity and hippocampus-dependent memory formation in adults. We addressed here the question of how PS-induced alterations in the immune response in young and old mice may contribute to changes in hippocampal function in aging. Immune stimulation (via LPS injection) significantly affected the ability of the hippocampal CA3-CA1 synapse of PS mice to undergo long-term potentiation (LTP). Elevated corticosterone level in the blood of aged PS mice that is known to influence LTP magnitude indicates a chronic activation of the HPA axis due to the in utero stress exposure. We investigated the contribution of adrenergic receptors to the modulation of hippocampal synaptic plasticity of aged mice and found that impaired LTP in the PS-LPS group was indeed rescued by application of isoproterenol (a nonspecific noradrenergic agonist). Further exploration of the mechanisms of the observed phenomena will add to our understanding of the interaction between PS and proinflammatory immune activation and its contribution to the functional and structural integrity of the aging brain.